IMPLICATIONS OF THE HEALTH CRISIS GENERATED BY THE COVID-19 PANDEMIC ON THE ROMANIAN LABOUR MARKET - Madalina BRUTU (Publishing house of University of Pitesti, Romania, 2020)
The International Labour Organization warns that the Pandemic will have devastating effects on the labour market, worldwide. It specified that an impressive number of employees have already been affected by the social distancing measures and that this crisis will be the worst for the labour market since World War II. The impact of the pandemic has been and is still strongly felt on the Romanian labour market as well. Most companies in the economy sent their employees in technical unemployment in the spring of 2020, and most employments are cancelled, postponed or frozen. The European Commission forecast that the Romanian economy will contract by 5.2% in 2020 and the deficit will grow by 10.3% of GDP. The hope for November 2020 comes from the pharmaceutical companies Pfizer and BioNTech who announced an efficacy of 90% of the Covid-19 vaccine and from which the European Commission has already contracted 300 million doses of vaccine, at a lower price than that the USA will pay.